Platelet function and soluble P-selectin in patients with primary immune thrombocytopenia. Issue 223 (March 2023) - Mehic, Dino; Machacek, Jennifer; Schramm, Theresa; Buresch, Lisbeth; Kaider, Alexandra; Eichelberger, Beate; Haslacher, Helmuth; Fillitz, Michael; Dixer, Barbara; Flasch, Tanja; Anderle, Theresa; Rath, Anja; et al.
Abstract: Background: The bleeding phenotype in immune thrombocytopenia (ITP) is heterogeneous, but usually mild and only partly dependent on the severity of thrombocytopenia. Platelet reactivity has previously been suggested to underly the mild phenotype. Methods: Platelet function was assessed as basal and agonist-induced surface expression of P-selectin and activation of GPIIb/IIIa via flow cytometry, and soluble (s)P-selectin levels were assessed in plasma of 77 patients with primary ITP, 19 hemato-oncologic thrombocytopenic controls (TC) and 20 healthy controls (HC). The association of platelet function with laboratory and clinical parameters such as bleeding manifestations at inclusion and previous thrombosis was analyzed. Results: ITP patients showed tendency towards increased surface P-selectin and elevated levels of activated GPIIb/IIIa. Platelet activation after stimulation with all agonists including TRAP-6, ADP, arachidonic acid and CRP was decreased compared to HC. Compared to TC, only GPIIb/IIIa activation but not surface P-selectin was higher in ITP. Levels of soluble (s)P-selectin were significantly higher in ITP patients compared to TC, but similar to HC. Higher sP-selectin levels were associated with blood group O and current therapy, with highest levels in TPO-RA treated patients. Platelet reactivity was not associated with platelet count or size, platelet antibodies, treatment regime, or blood group. No correlation between platelet activation with the bleeding phenotype or previous thrombotic events could be observed. Conclusion: ITP patients did not have hyper-reactive platelets compared to HC, but partly higher reactivity compared to TC. Further studies are needed to understand the underlying mechanism behind the bleeding and pro-thrombotic phenotype in ITP. 250/250. Graphical abstract: Unlabelled Image